(untitled) (Clinics, 2021)
OBJECTIVES: Thoracic aortic aneurysms (TAAs) represent one-third of the hospitalizations for aortic diseases. The prevalence rate depends on the definition of the normal size of the aorta, which is quite variable, depending on the population studied. The aim of this study was to evaluate the characteristics of the thoracic aorta of Brazilian smokers, identifying the normal size of the aorta, presence of anatomical variations, and prevalence of TAA. MATERIALS AND METHODS: A total of 711 patients underwent radiological evaluation with low-dose computed tomography (CT) from January 2013 to July 2014 with the initial objective of lung nodule tracking. Two examiners evaluated these images, and measurements of maximum and serial diameters were performed manually in true orthogonal planes. Serial diameter measurements were taken every 2 cm in the ascending aorta and 5 cm in the descending segment. We searched for anatomical variations, aortic arch type, and correlations between anatomical characteristics, sex, body mass index, and body surface area (BSA). RESULTS: The maximum diameters were 33.61 (standard deviation [SD] 3.88), 28.66 (SD 2.89), and 28.36 mm (SD 3.09) for the ascending segment, aortic arch, and descending segment, respectively. A positive correlation was found between male sex, age, and BSA and aorta diameter. The bovine arch was the most common variation of the aortic arch type, and we found one (0.14%) case of TAA. CONCLUSIONS: This study with low-dose CT allowed the determination of the mean diameters of the ascending aorta, aortic arch, and descending aorta in Brazilian smokers and TAA prevalence.